2019
DOI: 10.2147/imcrj.s194403
|View full text |Cite
|
Sign up to set email alerts
|

<p>Add-on administration of ultramicronized palmitoylethanolamide in the treatment of new-onset burning mouth syndrome</p>

Abstract: Aim The purpose of this study was to treat burning mouth syndrome (BMS) with a combination of painful gabapentin and ultramicronized palmitoylethanolamide (umPEA), in an attempt to improve the severe symptomatology of BMS. Methods We examined the case of a 60-year-old male, suffering from late-onset burning mouth syndrome. He found that gabapentin had a poor control of symptoms, thus we added umPEA, after administering a Visual Analog Scale (VAS), showing a score of 8–9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“… 51 Other antioxidant agents such as melatonin 58 and Alpha‐lipoic acid (ALA) have examined, the last of them having the highest number of clinical trial studies. The four case reports and case series studies have shown the therapeutic effects of antioxidant agents, methylene blue, 61 Chamomile, 57 ultramicronized palmitoylethanolamide 59 in secondary BMS patients (Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“… 51 Other antioxidant agents such as melatonin 58 and Alpha‐lipoic acid (ALA) have examined, the last of them having the highest number of clinical trial studies. The four case reports and case series studies have shown the therapeutic effects of antioxidant agents, methylene blue, 61 Chamomile, 57 ultramicronized palmitoylethanolamide 59 in secondary BMS patients (Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the clinical side, micro-PEA (i.e., micronized, ultramicronized or co-micronized PEA) has been orally administered as a dietary food for special medical purposes to human patients, either singly [ 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 , 220 , 221 , 222 , 223 , 224 , 225 ] or in combination with (i.e., add-on dietary intervention to) opioids, gabapentenoids or NSAIDs [ 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 , 234 , 235 , 236 , 237 , 238 , 239 , 240 , 241 , 242 , 243 , 244 , 245 , 246 , 247 , 248 ], as well as antioxidant compounds (e.g., luteolin, quercetin, polydatin) [ 249 , 250 , 251 , 252 , 253 , 254 , 255 , 256 , …”
Section: Clinical Evidence For Micro-pea Dietary Supplementation In Pain Reliefmentioning
confidence: 99%
“…To reduce the development of ADRs, which could be also related to the dosage and the long duration of treatment, a nonpharmacological treatment has been suggested. Nutrients are commonly used in patients with pain, e.g., Acetyl-L-carnitine [14][15][16][17][18][19][20], palmitoylethanolamide (PEA) [21][22][23][24][25][26][27], and alpha-lipoic acid [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%